EDUKASI PENCATATAN LAPORAN KEUANGAN SEDERHANA BAGI PELAKU USAHA MIKRO, KECIL DAN MENENGAH (UMKM) - Purwanto Purwanto; Dhea Yustiana Safitri; M. Pudail (As-Sidanah, 2023)
MSMEs, resilient and resistant to the economic crisis, can absorb labour, thereby reducing unemployment. Therefore, activities for MSMEs are needed to develop their business in a better direction. Tlogo Hamlet business actors still need to pay more attention to recording reports; there is no separation between personal money and business money, and lack of knowledge about the benefits of recording simple financial statements. The purpose of implementing community service activities in Education Report Recording for MSMEs in Tlogo Hamlet, Sutopati Kajoran Village, is to provide education and assistance to MSMEs related to recording financial statements, how to record and their benefits for businesses. Assisting MSMEs in implementing bookkeeping in their daily activities. The PAR (Participatory Action Research) method is the method of implementing this community service. To solve existing problems, the activities carried out consist of investigations, actions, and reflections. Inquiry is the stage where the team searches for problems and needs, which can obtain the main problems and programs needed. Action is the stage carried out to carry out the program, which consists of two activities: forming partnerships and implementing activities needed by partners. Partners in implementing this service consist of MSMEs actors, women farmer groups, and PKK groups. The reflection stage is the stage that shows the results of activities and reviews activities that have been carried out. The results of the community's implementation and research are aware of the benefits, understanding and increased knowledge about the importance of recording simple financial statements for business actors. This service activity implies that MSMEs actors, especially in Tlogo Hamlet, Sutopati Kajoran Village, can understand good ways of entrepreneurship through financial records to make it easier for them to develop achievements and know progress through cash inflow and outflow transaction activities.